Optimasi Bentuk Hip Stem Prosthesis untuk Kondisi Heel Strike dan Flat Foot dengan Menggunakan Topology Optimization Berbasis Metode Elemen Hingga - Syifaul Huzni; Syarizal Fonna; Heri Faisandra (Jurnal Teknik Mesin Unsyiah, 2018)
The objective of this research is to analyze the results of the topology optimization model Hip Stem Prosthesis in heel strike and flat foot conditions. The simulation is done using software based on finite element method ANSYS Release 18.0. Analysis of heel strike and flat foot conditions was carried out on the design of the artificial pelvic bone AML (Anatomical Modullary Locking) model. The ball head diameter used in this research was 38 mm and stem length was 140 mm. The analysis is done by optimizing the hip stem prosthesis step by step according to the condition when walking. Loading is given to the hip stem prosthesis during heel strike and flat foot with a time history of 0,01 seconds and 0,2 seconds starting from the initial position of heel strike and ending with the flat foot position. The simulation results show that the stress distribution is evenly distributed and the size of the volume of the design region varies.